Association of Neuropathological Markers in the Parietal Cortex With Antemortem Cognitive Function in Persons With Mild Cognitive Impairment and Alzheimer Disease. Issue 2 (31st January 2017) - Tremblay, Cyntia; François, Arnaud; Delay, Charlotte; Freland, Laure; Vandal, Milène; Bennett, David A; Calon, Frédéric
Abstract : The associations between cognitive function and neuropathological markers in patients with mild cognitive impairment (MCI) and Alzheimer disease (AD) remain only partly defined. We investigated relationships between antemortem global cognitive scores and β-amyloid (Aβ), tau, TDP-43, synaptic proteins and other key AD neuropathological markers assessed by biochemical approaches in postmortem anterior parietal cortex samples from 36 subjects (12 MCI, 12 AD and 12 not cognitively impaired) from the Religious Orders Study. Overall, the strongest negative correlation coefficients associated with global cognitive scores were obtained for insoluble phosphorylated tau ( r 2 = −0.484), insoluble Aβ42 ( r 2 = −0.389) and neurofibrillary tangle counts ( r 2 = −0.494) (all p < 0.001). Robust inverse associations with cognition scores were also established for TDP-43-positive cytoplasmic inclusions ( r 2 = −0.476), total insoluble tau ( r 2 = −0.385) and Aβ plaque counts ( r 2 = −0.426). Sarkosyl (SK)- or formic acid (FA)-extracted tau showed similar interrelations. On the other hand, synaptophysin ( r 2 = +0.335), pS403/404 TDP-43 ( r 2 = +0.265) and septin-3 ( r 2 = +0.257) proteins positively correlated with cognitive scores. This study suggests that tau and Aβ42 in their insoluble aggregated forms, synaptic proteins and TDP-43 are the markers in the parietal cortex that are most strongly associated with cognitive function. This further substantiates the relevance of investigating these markers to understand the pathogenesis of AD and develop therapeutic tools.